Pentakis(l-prolinium) dodecatungstoborate trihydrate - Raissi Shabari, Akbar (International Union of Crystallography, 2009)
The title polyoxometalate-based organic-inorganic hybrid compound, (C(5)H(10)NO(2))(5)[BW(12)O(40)]·3H(2)O, consists of one α-Keggin-type [BW(12)O(40)](5−) polyoxoanion, five crystallographically independent l-prolinium cations and three uncoordinated water molecules. The polyoxoanion shows characteristic features with respect to bond lengths and angles. Several N—H⋯O and O—H⋯O hydrogen bonds between the organic cations, inorganic anions and crystal water molecules lead to a three-dimensional supramolecular structure.